Vascular dynamics during laissez-faire healing in periocular defects assessed with laser speckle contrast imaging - Vennström Berggren, Johanna ; 0000-0003-2009-8183; Nääv Ottosson, Jens; Tenland, Kajsa; Naumovska, Magdalena; Fontana, Morgana; Merdasa, Aboma ; 0000-0002-6298-5672; Malmsjö, Malin ; 0000-0001-9849-9599 (Orbit, 2025)
Purpose: To evaluate the role of blood perfusion and revascularization during the healing process of periocular defects treated with laissez-faire following tumor excision. Methods: Ten patients with periocular basal cell carcinomas underwent excision, followed by laissez-faire wound management. Blood perfusion was measured using laser speckle contrast imaging postoperatively. Results: Immediately after excision, perfusion increased in the wound edge and the peri-wound tissue, reaching approximately 157% of reference values (p < 0.01), reflecting immediate effects of surgery. At 1 week, perfusion increased further, likely driven by inflammation and angiogenesis (193%, p < 0.001). Perfusion gradually decreased at 6–8 weeks, aligning with active tissue remodeling, and continued to normalize at 4–5 months (123%, p > 0.05). By 12 months, perfusion returned to baseline levels, reflecting wound maturation (109%, p > 0.05). In cases with directing sutures, perfusion initially decreased to 64% at the wound edge, presumably due to tension-induced hypoperfusion, but returned to baseline after 6–8 weeks. Conclusion: This study highlights the critical role of blood perfusion in the healing of periocular defects treated with laissez-faire. The vascular network is preserved, enabling an immediate increase in perfusion, facilitating revascularization and wound healing. Further studies are needed to evaluate efficacy and long-term outcomes in comparison with reconstructive surgery.
Keywords: Blood flow; laissez-faire; perfusion monitoring